Measuring event participants - Kim, Boram (Proceedings of the Amsterdam Colloquium, 2024)
Measure nouns like percent can be interpreted reverse proportionally, as in “The company hired 50% women.” The most influential analyses of this phenomenon derive it via association with focus, which is known to invert restrictor-scope relations for adnominal markers like only and few. I offer three arguments that reverse proportional readings in Korean are not focus-sensitive, and are instead simply adverbial modifiers quantifying over event participants, in the spirit of Nakanishi’s (2007) analysis of bare numerals. I suggest that this opens the door to possible re-analyses of the data crosslinguistically.